Enhancing the anticancer potential of metformin: fabrication of efficient nanospanlastics, in vitro cytotoxic studies on HEP-2 cells and reactome enhanced pathway analysis - Shereen Nader Raafat; Sara Abd El Wahed; Noha M. Badawi; Mona M. Saber; Maha R.A. Abdollah (Elsevier, 2023)
Metformin (MET), an oral antidiabetic drug, was reported to possess promising anticancer effects. We hypothesized that MET encapsulation in unique nanospanlastics would enhance its anticancer potential against HEP-2 cells. Our results showed the successful fabrication of Nano-MET spanlastics (d = 232.10 ± 0.20 nm; PDI = 0.25 ± 0.11; zeta potential = (−) 44.50 ± 0.96; drug content = 99.90 ± 0.11 and entrapment efficiency = 88.01 ± 2.50%). MTT assay revealed the enhanced Nano-MET cytotoxicity over MET with a calculated IC50 of 50 μg/mL and > 500 μg/mL, respectively. Annexin V/PI apoptosis assay showed that Nano-MET significantly decreased the percentage of live cells from 95.49 to 93.70 compared to MET and increased the percentage of cells arrested in the G0/G1 phase by 8.38%. Moreover, Nano-MET downregulated BCL-2 and upregulated BAX protein levels by 1.57 and 1.88 folds, respectively. RT-qPCR revealed that Nano-MET caused a significant 13.75, 4.15, and 2.23-fold increase in caspase-3, −8, and − 9 levels as well as a 100 and 43.47-fold decrease in cyclin D1 and mTOR levels, respectively. The proliferation marker Ki67 immunofluorescent staining revealed a 3-fold decrease in positive cells in Nano-MET compared to the control. Utilizing the combined Pathway-Enrichment Analysis (PEA) and Reactome analysis indicated high enrichment of certain pathways including nucleotides metabolism, Nudix-type hydrolase enzymes, carbon dioxide hydration, hemostasis, and the innate immune system. In summary, our results confirm MET cytotoxicity enhancement by its encapsulation in nanospanlastics. We also highlight, using PEA, that MET can modulate multiple pathways implicated in carcinogenesis.